PENENTUAN JARAK BATU TERBANG MENGGUNAKAN METODE LINTASAN DI KUARI ANDESIT PT. NSM PURWAKARTA - Awang Suwandhi; Wanda Adinugraha; Dwihandoyo Marmer; Maikel Kambuaya (PPSDM Geominerba, 2022)
One of the problems in blasting is the presence of fly rocks which can have a serious impact on the surrounding environment, especially when hit by humans and infrastructure. To determine the horizontal distance of fly rocks is usually conducted by measuring the coordinates of the blasting point to the point where the rock fell to the ground. The video Tracker method approach is used to determine the farthest horizontal distance through its path. Based on the same blasting geometry, it was found that the equivalence of the horizontal distance of fly rocks using the video Tracker reached 97% of the coordinate measurement method. Meanwhile, the fly rocks distance resulting from the measurement method cannot be equated with the intrinsic or theoretical approach which is predictive in nature. The effect of total explosives used is quite significant on the occurrence of fly rocks. The more explosives used, the farther the fly rocks will be thrown. The incident of rocks being thrown away as a result of explosions at PT. NSM reached 95.60% due to the amount of explosives.